Intratympanic delivery of oligoarginine-conjugated nanoparticles as a gene (or drug) carrier to the inner ear. (December 2015) - Yoon, Ji Young; Yang, Keum-Jin; Kim, Da Eun; Lee, Kyu-Yup; Park, Shi-Nae; Kim, Dong-Kee; Kim, Jong-Duk
Abstract: A drug delivery system to the inner ear using nanoparticles consisting of oligoarginine peptide (Arg8) conjugated to poly(amino acid) (poly(2-hydroxyethyll -aspartamide; PHEA) was investigated to determine whether the limitations of low drug transport levels across the round window membrane (RWM) and poor transport into inner ear target cells, including hair cells and spiral ganglion, could be overcome. Three types of carrier materials, PHEA-g-C18, PHEA-g-Arg8, and PHEA-g-C18-Arg8, were synthesized to examine the effects of oligoarginine and morphology of the synthesized carriers. Nile red (NR) was used as a fluorescent indicator as well as to model a hydrophobic drug. Compared with PHEA-g-C18-NR nanoparticles, the oligoarginine-conjugated nanoparticles of PHEA-g-C18-Arg8-NR and PHEA-g-Arg8-NR entered into HEI-OC1 cells at significant levels. Furthermore, the strongest fluorescence intensity was observed in nuclei when PHEA-g-C18-Arg8 nanoparticles were used. The high uptake rates of PHEA-g-C18 and PHEA-g-C18-Arg8 nanoparticles were observed in ex vivo experiments using hair cells. After the delivery of PHEA-g-C18-Arg8 nanoparticles with reporter gene transfer, EGFP (enhanced green fluorescent protein) expression was monitored as an indicator of gene delivery. In the inner ear cells, PHEA-g-C18-Arg8 nanoparticles showed comparable or better transfection capabilities than the commercially available Lipofectamine reagent. PHEA-g-C18-Arg8 penetrated in vivo across the RWM of C57/BL6 mice with Nile red staining and GFP expression in various inner ear tissues. In conclusion, PHEA-g-C18-Arg8 nanoparticles were successfully transported into the inner ear through the intratympanic route and are proposed as promising candidates as delivery carriers to address inner ear diseases.